PARASITISM ASSOCIATED WITH LENGTH AND GONADAL MATURITY STAGE OF THE FRESHWATER FISH METYNNIS LIPPINCOTTIANUS (CHARACIDAE) - Hideki Yamada, Fábio (2012)
Parasitism was observed in 72.7% of 44 specimens of Metynnis lippincottianus (Cope, 1870) (Characidae) caught in the Upper Paraná River floodplain, Brazil. One species of digenean, Dadayus pacupeva Lacerda, Takemoto & Pavanelli, 2003, and four species of nematodes, Spinoxyuris oxydoras Peter, 1994, Contracaecum sp. Railliet & Henry, 1912 (larval stage), Procamallanus (Spirocamallanus) inopinatus Travassos, Artigas & Pereira, 1928 and Raphidascaris (Sprentascaris) mahnerti Petter & Cassone, 1984 were identified. The prevalence of D. pacupeva was correlated with the host's standard length. Correlations between the host's standard length and the abundance of S. oxydoras, P. (S.) inopinatus and D. pacupeva were observed. In addition, fish length was correlated with the diversity of parasites. D. pacupeva and S. oxydoras had their abundances influenced by the host's gonadal maturity stage. According to gonadal maturity stage, the host may or may not have an increased susceptibility to parasites, suggesting a cumulative process causing higher parasite abundance in larger fish and in the mature stage (more time of exposure) than the immature stage (young fish).